To What Extent Is The Governance of Local Public Service Innovation In Indonesia? - Suranto Suranto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study critically examines the extent to which the governance of local public service innovation in Indonesia operates within and beyond its formal legal and institutional frameworks. Employing an empirical legal research design grounded in qualitative analysis, the study draws on multiple case studies, including innovations implemented in Bantul Regency, Kubu Raya Regency, and Batam City, supported by in depth interviews, document analysis, and field observations. The findings reveal that while Indonesia has established a comprehensive regulatory architecture through Law Number 25 of 2009, Law Number 23 of 2014, Law Number 30 of 2014, Government Regulation Number 38 of 2017, and Ministerial Regulation Number 30 of 2014, the practical governance of innovation remains uneven and fragmented. Normative compliance does not consistently translate into effective implementation, participatory inclusiveness, or sustainable institutionalisation. The study demonstrates that governance outcomes are shaped by the interaction between regulatory structures, administrative capacity, digital transformation, and accountability mechanisms. It argues that strengthening legal integration, institutional coherence, and performance based accountability is essential for ensuring that local public service innovation contributes meaningfully to governance effectiveness and public value creation.